Nanofibrous Scaffolds’ Ability to Induce Mesenchymal Stem Cell Differentiation for Soft Tissue Regenerative Applications - Silvia Pisani; Aleksandra Evangelista; Luca Chesi; Stefania Croce; Maria Antonietta Avanzini; Rossella Dorati; Ida Genta; Marco Benazzo; Patrizia Comoli; Bice Conti (Pharmaceuticals)
Mesenchymal stem cells (MSCs) have gained recognition as a highly versatile and promising cell source for repopulating bioengineered scaffolds due to their inherent capacity to differentiate into multiple cell types. However, MSC implantation techniques have often yielded inconsistent clinical results, underscoring the need for advanced approaches to enhance their therapeutic efficacy. Recent developments in three-dimensional (3D) bioengineered scaffolds have provided a significant breakthrough by closely mimicking the in vivo environment, addressing the limitations of traditional two-dimensional (2D) cell cultures. Among these, nanofibrous scaffolds have proven particularly effective, offering an optimal 3D framework, growth-permissive substrates, and the delivery of trophic factors crucial for MSC survival and regeneration. Furthermore, the selection of appropriate biomaterials can amplify the paracrine effects of MSCs, promoting both proliferation and targeted differentiation. The synergistic combination of MSCs with nanofibrous scaffolds has demonstrated remarkable potential in achieving repair, regeneration, and tissue-specific differentiation with enhanced safety and efficacy, paving the way for routine clinical applications. In this review, we examine the most recent studies (2013–2023) that explore the combined use of MSCs and nanofibrous scaffolds for differentiation into cardiogenic, epithelial, myogenic, tendon, and vascular cell lineages. Using PubMed, we identified and analyzed 275 relevant articles based on the search terms “Nanofibers”, “Electrospinning”, “Mesenchymal stem cells”, and “Differentiation”. This review highlights the critical advancements in the use of nanofibrous scaffolds as a platform for MSC differentiation and tissue regeneration. By summarizing key findings from the last decade, it provides valuable insights for researchers and clinicians aiming to optimize scaffold design, MSC integration, and translational applications. These insights could significantly influence future research directions and the development of more effective regenerative therapies.